Nursing care for maintenance and prevention of enteral probe loss - Roberto, Elisangela de Lourdes Moreira Araújo; Silvestre, Simone Chaves de Miranda; Beinner, Mark Anthony; Oliveira, Suelen Rosa de (Revista de Enfermagem da UFPI, 2024)
Objective: To understand the perception and practice of nursing professionals about care related to the maintenance and prevention of enteral probe loss in hospitalization units. Methods: Quanti-qualitative and descriptive study carried out in a large general hospital in Belo Horizonte, Minas Gerais, Brazil. It was attended by 40 professionals, 19 nurses and 21 nursing technicians, interviewed in September and October 2018. Secondary data were collected from the medical records of 114 patients who were using an enteral probe from 01/01/2017 to 01 /01/2018. Results: It was observed that the majority (68.4%) of patients undergoing enteral nutritional therapy were over 60 years of age. Nutritional causes were the main indication for the use of probes, occurring in 51.7% of patients. Most (90.0%) of professionals recognize that washing the probe is the main care in terms of preventing loss of this device and recognize that the biggest complication of its use is bronchoaspiration. Conclusion: It was found that nursing professionals have knowledge about care related to maintenance and prevention of probe loss, but the perception of these professionals is different from the information introduced in the medical records, which may highlight a disarticulation between knowledge and care practice.